DETERMINE THE PROBABILITY OF PASSENGER SURVIVAL IN AN AVIATION INCIDENT WITH FIRE ON THE GROUND - Vladislav Pavlovich Turko (International Journal of Advanced Studies, 2017)
Conducting the risk level of aviation incident with fire and the impacts of contingence affecting factors on people. Base on statistical data of aviation incident, the model of aircraft fire situation on the ground was offer.